Estudio de factibilidad para la creación de una empresa de procesamiento y comercialización de piña deshidratada en trozos en la ciudad de Cali (2013)
The following paper is aim to describe and identify the potential growth of the food for human consumption sector. In this case the dried chunks of fruit (pineapple) to be sold in the region of Valle del Cauca. The following research is for a feasibility study for the creation of a marketer and processor of dried pineapple chunks in the city of Cali. The fruit product in chunks is the raw material for the manufacture of various processed foods such as: cakes, ice cream, pizza, sauces, among others. There is also the habit of eating fruit in its natural state. That is the reason why the demand for this product is always increasing. Due to its geographical conditions and variety of climatic zones, Colombia has the ability to produce a wide range of high quality fruits. The objective of the feasibility study for the creation of a commercial dried fruit is to achieve the high demand for fruit that exists in the region of Valle del Cauca; mainly in the city of Cali. Within the main activities, is to market with this type of fruit in hotels, restaurants, ice cream parlors, bakeries and in the district 19 of this city. District 19 is selected as the target market in the City of Cali because of its demographics and especially because of the consumption habits of the population. Being close to establishments such as: hotels, ice cream shops, chain stores, these are related to the consumption of these type preparations of fruit desserts, juices, and snacks, among others. Thus, to determine the feasibility project, a comprehensive analysis of the different variables of the horticultural sector is done, so it will identify opportunities that exist in the domestic consumption of the product under study. Initially, an analysis of demand and supply of the product in the target market is done, and then we proceed to the analysis of environments, in order to identify the rate of growth of horticulture, market size, competition settings and administrative and operational risks. Additionally, there will be a financial assessment of future company called FRUTITROZOS S.A.S., identifying the cost of the necessary resources; we will project the revenues from sales, and the operating expenses. Similarly, we will conduct an analysis of the organizational design that the company will need in order to distribute the roles and responsibilities among its employees. This research will allow the application of theoretical concepts in finance, technical, personnel and marketing, area. To carry out the objectives of this work, we will be using a causal or explanatory methodology, based on the current situation of horticulture especially pineapple in its natural state. Then, we will proceed with the dehydration process and deliver it in chucks to the consumers located in the region of Valle del Cauca district 19 and other companies interested in the type of fruit that the company will offer